2009
DOI: 10.1016/j.cortex.2008.10.013
|View full text |Cite
|
Sign up to set email alerts
|

The temporal characteristics of functional activation in Broca's area during overt picture naming

Abstract: Picture namingBroca's area Language production Speech production a b s t r a c tThe opercular and triangular sections of the inferior frontal gyrus, also known as Broca's area, have been shown to be involved in various language tasks. In the current study we investigated both the functional role, as well as the precise temporal involvement of Broca's area during picture naming. We applied online event-related transcranial magnetic stimulation (TMS) to Broca's area at five different time points after picture pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
84
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(91 citation statements)
references
References 29 publications
7
84
0
Order By: Relevance
“…This discrepency may have resulted from the fact that previous studies did not separately examine planning and execution processes in which the left IFG may play different roles. Evidence on normal speech indicates that the left IFG is mainly involved in syllabification (Schuhmann et al, 2008) or phonetic encoding (Papoutsi et al, 2009), both of which are related to the internal construction of motor plan of speech acts (Moser et al, 2009;Schnur et al, 2009). Thus, our results not only confirmed the involvement of the left IFG in stuttering, but also strongly suggested a key role of the left IFG in atypical planning process in stuttering.…”
Section: The Neural Substrates For Atypical Planning Process In Stuttmentioning
confidence: 99%
“…This discrepency may have resulted from the fact that previous studies did not separately examine planning and execution processes in which the left IFG may play different roles. Evidence on normal speech indicates that the left IFG is mainly involved in syllabification (Schuhmann et al, 2008) or phonetic encoding (Papoutsi et al, 2009), both of which are related to the internal construction of motor plan of speech acts (Moser et al, 2009;Schnur et al, 2009). Thus, our results not only confirmed the involvement of the left IFG in stuttering, but also strongly suggested a key role of the left IFG in atypical planning process in stuttering.…”
Section: The Neural Substrates For Atypical Planning Process In Stuttmentioning
confidence: 99%
“…This is because of the increasing realization that brain imaging data represents an additional dependent variable of relevance to spreading activation models (e.g., Goldrick, 2007;Dell & Sullivan, 2004). There is now a large literature relating brain activation data to stages of processing in models of spoken word production (e.g., Acheson, Hamidi, Binder, & Postle, 2011;Peeva et al, 2010;Schuhmann, Schiller, Goebel, & Sack, 2009;Alario, Chainay, Lehericy, & Cohen, 2006;Indefrey & Levelt, 2004). These studies have identified roles for the midsection of the left middle temporal gyrus in lexical semantic processing and the posterior section of the middle and superior temporal gyri ( Wernickeʼs area) in phonological word form retrieval, respectively, within a predominantly left hemisphere cerebral network.…”
Section: Introductionmentioning
confidence: 99%
“…These studies have identified roles for the midsection of the left middle temporal gyrus in lexical semantic processing and the posterior section of the middle and superior temporal gyri ( Wernickeʼs area) in phonological word form retrieval, respectively, within a predominantly left hemisphere cerebral network. During naming of depicted objects, the time course of activation in these two regions typically occurs between 150 and 300 msec following initial visual object recognition, with postlexical processes of syllabification and phonetic encoding followed by articulation occurring between 300 and 600 msec attributed to the posterior left inferior pFC (Brocaʼs area) and premotor cortical areas, respectively (e.g., Acheson et al, 2011;Schuhmann et al, 2009;Indefrey & Levelt, 2004). Consequently, these studies provide candidate brain regions for testing the "input" and "output" accounts.…”
Section: Introductionmentioning
confidence: 99%
“…In other words, the question is whether all encoding processes from concept to articulation are stretched in slow speakers relative to fast speakers, or if processing speed is associated with variable encoding times for a particular process. Schuhmann et al (2009) had to deal with the interpretation of which encoding process was associated with a specific time period in subjects with very short production latencies (during the production of a limited number of monosyllabic words): They hypothesized that speed affects all the processes involved in speech production equally.…”
Section: Introductionmentioning
confidence: 99%
“…Taking advantage of topographic (spatio-temporal) ERP analyses (Murray, et al, 2008;Michel et al, 2009), we examined the duration of specific electrophysiological patterns (functional microstates, Lehmann, 1987;Michel et al, 2009) across slow and fast speakers and their correlation with production latencies. If speed of word production is distributed along all the speech encoding processes as hypothesised by Schuhmann et al (2009), then differences between slow and fast speakers should be observed in several time windows from the moment a picture appears on the screen to articulation. On the other hand, if differences in processing speed are linked to a specific encoding process, then ERP divergences between slow and fast speakers should be limited to a given time window, which can be associated to a specific encoding process.…”
mentioning
confidence: 99%